Rs12603332 is associated with male asthma patients specifically in urban areas of Lahore, Pakistan. (21st October 2017) - Sabar, Muhammad Farooq; Shahid, Mariam; Bano, Iqbal; Ghani, Muhammad Usman; Akram, Muhammad; Iqbal, Farheena; Kousar, Samra; Iqbal, Zafar; Altaf, Saba; Husnain, Tayyab
ABSTRACT: Objective : rs12603332, an important regulatory site variant, is known to alter the regulatory motif E2A that is involved in the maturation of B-lymphocytes. The study was designed to check whether different environmental exposures alter its risk allele association with asthma or not. Methods : 200 Physician-diagnosed asthma patients and 108 healthy individuals were enrolled from hospitals of Lahore. After quantitation of DNA extracted from peripheral blood, amplification of genomic region with rs12603332, followed by single base extension (SBE), was performed. Allele and genotype frequencies were calculated by SHEsis and Haploview software packages. Statistical analyses on PLINK were also performed, taking different factors as covariates. HaploReg analysis was done to predict the effect of risk allele on different regulatory motifs. Results : Risk allele for rs12603332 i.e., "C" allele was found to be significantly associated with male patients residing in urban localities. Conclusion : The finding suggests that on exposure with urban environment, risk allele carriers tend to develop asthma symptoms via epigenetic regulation of motif associated with maturation of B-lymphocytes.